1994
DOI: 10.1139/z94-204
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use by sympatric female mallards and American black ducks breeding in a forested environment

Abstract: There has been much speculation regarding whether breeding mallards (Anas platyrhynchos) and American black ducks (A. rubripes) use similar habitat types in forested areas, which could lead to increased interspecific contact. To study this issue, we used radiotelemetry during 1990–1991 on sympatric female mallards and black ducks breeding in the western Adirondack Mountains of New York. Mallard and black duck pairs occupied the general area at a density of 0.7 and 0.6/km2, respectively. Black duck home ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
4
13
2
Order By: Relevance
“…Our estimate of local breeding-season survival (0.726) is the lowest reported estimate for any northern-latitude breeding duck (Ringleman and Longcore 1983;Cowardin et al 1985;Kirby and Cowardin 1986;Dwyer and Baldassarre 1993;Petrie et al 2000). If we exclude non-breeders, our estimate is even lower (0.675, see Results).…”
Section: Female Survivalcontrasting
confidence: 56%
“…Our estimate of local breeding-season survival (0.726) is the lowest reported estimate for any northern-latitude breeding duck (Ringleman and Longcore 1983;Cowardin et al 1985;Kirby and Cowardin 1986;Dwyer and Baldassarre 1993;Petrie et al 2000). If we exclude non-breeders, our estimate is even lower (0.675, see Results).…”
Section: Female Survivalcontrasting
confidence: 56%
“…Breeding Mallards in northeastern North America use forested landscapes and select for scrub‐shrub wetlands within that landscape (Dwyer & Baldassarre 1994; Losito & Baldassarre 1995); in PEI we found a similar association in restored wetlands. Higher use of scrub‐shrub wetlands with a forested perimeter by Mallards suggests that these wetland types may be important due to the cover and subsequent visual isolation that they provide.…”
Section: Discussionmentioning
confidence: 50%
“…Mitochondrial (mt) DNA haplotypes are polyphyletic among these taxa, suggesting a recent radiation (Avise et al 1990, McCracken et al 2001, Lavretsky et al 2014, and ongoing hybridization between Mallards and each of the monochromatic species complicates phylogenetic inferences (Heusmann 1974, Hubbard 1977, Avise et al 1990, Dwyer and Baldassarre 1993, Merendino et al 1993, McCracken et al 2001, Pérez-Arteaga et al 2002, Pérez-Arteaga and Gaston 2004, Williams et al 2005a). Lavretsky et al (2014), for example, demonstrated that the posterior support for the NW monochromatic taxa doubled when Mallards were excluded, suggesting a confounding effect of contemporary introgression.…”
Section: Study Systemmentioning
confidence: 99%
“…Once found primarily west of the Mississippi River, environmental degradation (Livezey 1991, Green 1996, Mank et al 2004) and release programs (Heusmann 1974, Soutiere 1986, Hepp et al 1988 caused an expansion of the Mallard's range across North America leading to increased interspecific competition and hybridization with the monochromatic endemics. Growing interactions with Mallards have negatively influenced Black Duck populations since the 1950s (Ankney et al 1987, Avise et al 1990, Dwyer and Baldassarre 1993, Merendino et al 1993, Rhymer 2006), leading to concerns over the possibility of extinction by introgressive hybridization (Rhymer and Simberloff 1996). Moreover, the taxonomy of both Mexican Ducks (Hubbard 1977, Pérez-Arteaga et al 2002 and Mottled Ducks (Bielefeld et al 2010) have gone through various revisions, and continue to be debated.…”
Section: Study Systemmentioning
confidence: 99%